SIMULAÇÃO ACÚSTICA PARA UMA PEQUENA SALA MULTIUSO DE ENSINO E PRÁTICA MUSICAL - Lima, Pollyanna Rodrigues; Vergara, Erasmo Felipe; Lima, Diana Carla Rodrigues (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
For the musician enjoy a satisfactory experience in your musical practice environment a specific acoustic design is essential. The main objective of this work was to demonstrate the contribution of computational acoustics simulation on possibility of adaptation of an existing multipurpose classroom for teaching and musical practice. The main acoustic parameters of the room were obtained experimentally and later, different alternatives were tested using the computer simulation using Odeon software in order to obtain a model that suited the room to the musical practice. This model underwent several adaptations until it resulted in a room with values of acoustic parameters within the desirable limits, being, in the octave frequency bands of 500 to 1000 Hz: TR 1.34 s; EDT 1.40 s; C80 1.61 dB; D50 56.25%; STI 0.54. The resulting computational model allowed to adapt the multipurpose room, modeled for different realities, to the musical practice considering in this model the insertion or removal of acoustic materials and devices.